Belomarinaite KNa(SO4): A new sulfate from 2012–2013 Tolbachik Fissure eruption, Kamchatka Peninsula, Russia. (21st January 2019) - Filatov, Stanislav K.; Shablinskii, Andrey P.; Vergasova, Lidiya P.; Saprikina, Olga U.; Bubnova, Rimma S.; Moskaleva, Svetlana V.; Belousov, Alexander B.
Abstract: Belomarinaite, ideally KNaSO4, is a new sulfate mineral discovered in the Toludskoe lava field, formed during the 2012–2013 Tolbachik Fissure eruption. The mineral occurs as arborescent aggregates of tabular crystals (1 mm × 0.3 mm × 0.1 mm) comprising hematite impurities. The average size of the aggregates is 0.5–0.7 mm. The empirical formula is (K0.95 Na0.92 Cu0.04 )Σ1.91 S1.01 O4 . The crystal structure of belomarinaite was determined using single-crystal X-ray diffraction data; the space group is P 3 m 1, a = 5.6072(3), c = 7.1781(4) Å, V = 195.45(2) Å 3, Z = 2 and R 1 = 2.6%. In the crystal structure of belomarinaite, there are six cation sites: the [4] S 1 and [4] S 2 sites are occupied by S, the [6] Na and [12] K sites are occupied by Na and K, respectively, giving Na0.5 K0.5 apfu and the [10] M 1 and [10] M 2 sites are occupied by Na0.78 K0.22 and K0.78 Na0.22 apfu, respectively. The crystal structure is a framework of SO4 tetrahedra, Na octahedra and K, M 1 and M 2 polyhedra. Belomarinaite is isostructural with the synthetic compound KNaSO4 . In belomarinaite, Na and K are disordered over M 1 and M 2 sites; in its synthetic analogue, Na and K are ordered over M 1 and M 2 sites, respectively. The Mohs' hardness is 2–3. The mineral is uniaxial (+), with ω = 1.485(3) and ε = 1.488(3) (λ = 589 nm). The strongest lines of the powder X-ray diffraction pattern [ d, Å ( I, %) ( hkl )] are: 4.022(31)(101); 3.591(26)(002); 2.884(74)(102); 2.800(100)(110); 2.391(16)(003); 2.296(8)201; 2.008(38)(022); and 1.634(10)(212). The mineral was named in honour of Russian volcanologist Marina Gennadievna Belousova (b. 1960) for her significant contributions to the monitoring of the Tolbachik Fissure eruption.